Alleviating unemployment traps in Finland: Can the efficiency-equity trade-off be avoided? - Pertti Honkanen; Markus Jäntti; Jukka Pirttilä (Aboa Centre for Economics (ACE), 2007)
Using a new comprehensive tax-benefit model, JUTTA, this paper examines how labour supply incentives – both to participate in the labour force (the “extensive” margin) and to supply extra hours of work (the “incentive” margin) – have changed in Finland in 1995-2007. The results reveal that the average participation tax rate has decreased by 10 percentage points to 62 per cent. Despite the significant improvement in incentives, some of the unemployed who have children, especially single parents, are still in an unemployment trap, i.e. the disposable family income does not significantly increase if the person is employed. We therefore present simulations where the social security system is reformed, without reducing minimum benefits, so that the income dependence of some of the benefits is reduced. This reform redistributes income to the poor and, at the same time, improves the incentives to participate in the labour force. We also compare the effects of this policy with those of a set of more traditional type of policies, consisting of across-the-board tax cuts and increases in income support.
Keywords: H24; I38; J22; 330; microsimulation; labour supply; extensive margin; efficiency-equity trade-off